Triboelectric nanogenerators: Fundamental physics and potential applications - Linglin Zhou; Di Liu; Jie Wang; Zhong Lin Wang (Friction)
Abstract Based on the conjunction of contact electrification and electrostatic induction, triboelectric nanogenerators (TENGs) can harvest mechanical energy dispersed in our environment. With the characteristics of simple structure, light weight, broad material availability, low cost, and high efficiency even at low operation frequency, TENG can serve as a promising alternative strategy for meeting the needs of distributed energy for the internet of things and network. The major potential applications of TENG can be summarized as four fields containing micro/nano power sources, self-powered sensors, large-scale blue energy, and direct high-voltage power sources. In this paper, the fundamental physics, output performance enhancement, and applications of TENGs are reviewed to timely summarize the development of TENGs and provide a guideline for future research.